Hidden Objective Memory Deficits Behind Subjective Memory Complaints in Patients With Temporal Lobe Epilepsy. (22nd February 2022) - Lemesle, Béatrice; Barbeau, Emmanuel J.; Milongo Rigal, Emilie; Denuelle, Marie; Valton, Luc; Pariente, Jérémie; Curot, Jonathan
Abstract : Background and Objectives: The aim of this work was to test the hypothesis that patients with temporal lobe epilepsy (TLE) with subjective initial memory complaints (not confirmed by an objective standard assessment) and various phenotypes also show objective very long-term memory deficit with accelerated long-term forgetting. We tested patients with TLE with 2 surprise memory tests after 3 weeks: the standard Free and Cued Selective Reminding Test (FCSRT) and Epireal, a new test specifically designed to capture more ecologic aspects of autobiographical memory. Methods: Forty-seven patients with TLE (12 with hippocampal sclerosis, 12 with amygdala enlargement, 11 with extensive lesions, 12 with normal MRI) who complained about their memory, but for whom the standard neuropsychological assessment did not reveal any memory impairment after a standard delay of 20 minutes, underwent 2 surprise memory tests after 3 weeks. They were compared to 35 healthy controls. Results: After 3 weeks, FCSRT and Epireal recall scores were significantly lower in patients than in controls ( p < 0.001). There was no significant correlation between FCSRT and Epireal scores ( p = 0.99). Seventy-six percent of patients with TLE had objective impairment on at least 1 of these very long-term memory tests, regardless of the existence and type of lesion or response to antiseizure medication. Easily applicable, Epireal had a higher effect size, detected deficits in 28% more patients, and is a useful addition to the standard workup. Discussion: Assessing long-term memory should be broadened to a wide spectrum of patients with TLE with a memory complaint, regardless of the epileptic syndrome, regardless of whether it is associated with a lesion. This could lead to rethinking TLE nosology associated with memory.